The Mexican Revolution : conflict and consolidation, 1910-1940 - Richmond, Douglas W., 1946-; Haynes, Sam W. (Sam Walter), 1956-; Villanueva, Nicholas (Walter Prescott Webb memorial lectures ;, 2013)
In 1910, insurgent leaders crushed the Porfirian dictatorship, but in the years that followed fought among themselves - until a nationalist consensus produced the 1917 Constitution. This in turn provided the basis for a reform agenda that transformed Mexico in the modern era. The civil war and the reforms that followed receive insightful attention in this book. These essays, the result of the 45th annual Walter Prescott Webb Memorial Lectures, presented by the University of Texas at Arlington in March 2010, commemorate the centennial of the outbreak of the revolution.